A design project on the manufacture of newsprint from bagasse - Lopez, Ella Vina C. (College of Engineering, 1973)
Capacity: 11,260 MT/year -- Plant area: 97,200 sq. ft. -- Fixed capital investment: 22,055,963 -- Total capital investment: 25,954,636 -- Total manufacturing cost: 12,540,312 -- Annual sales at maximum production: 14,927,850 -- Annual profit: 2,387,542 -- Return on investment: 10.8% -- Pay-out time: 7.9 years -- Break-even point: 22%